Implementasi Sinkronisasi Database Berbasis RESTful Web Services pada Aplikasi Presensi - Deny Kristianto Pamuji; Mahmud Yunus; Dinny Wahyu Widarti (Universitas Widyagama Malang, 2020)
3PM Solution is one company with high employee mobility. To make a presence, a mobile presence system uses an application, so employees do not have to be present in the official to attend. However, new problems arise when employees cannot to the internet, which causes employees to be unable to attend. To overcome these problems, a synchronization method will be implemented which allows the application to run offline so that it does not have dependency on the internet network. Based on the research result obtained that the synchronization method is able to make the presence application run offline. The application is able to get 100% success from a total a 25 repetitions of offline attendance simulation and synchronization of attendance data in the testing process.